Instructed Concept Appropriation and L2 Pragmatic Development in the Classroom. Issue 3 (21st July 2014) - van Compernolle, Rémi A.; Henery, Ashlie
<x xml:space="preserve">Abstract</x> In this article, we investigate the integration of concept‐based pragmatics instruction, grounded in Vygotskian sociocultural psychology, in an intact second‐semester French class (n = 13) over the course of an academic term. Our focus is on learners' appropriation of the concepts of self‐presentation, social distance, and power with respect to the French second‐person pronoun system (i.e., tu versus vous) as revealed through language awareness questionnaires, appropriateness judgment tasks, and computer‐mediated strategic interaction scenario performances. Following this three‐tiered approach to analysis, our findings show that learners developed a deeper and more systematic understanding of tu and vous, that they were able to apply the concepts in planning language use, and that their use of tu and vous became more sensitive to maintaining symmetrical social relationships.